Bias dependent and scalable small-signal modeling of pseudomorphic HEMTs - Verma A.K.; Chaturvedi S.; Bhat K. M.; Saravanan G.S.; Muralidharan R. (My University, 2025)
Results of small-signal modeling of 0.5um gate length pseudomorphic HEMTs are presented here. Modeling included scalability with respect to number of gate fingers, gate width and gate bias dependence of Equivalent Circuit Parameters (E.C.Ps). p-HEMTs with gate widths of 100 μm and 150 μm, each with varying number of gate fingers (2, 4, 6) keeping all other structural parameters constant were fabricated for this study. To find small-signal E.C.Ps we used method proposed by Dambrine et.al. [2] and White-Healy [3]. On-wafer measurement of S-parameters for all devices was done from 100 MHz to 40 GHz under different bias-conditions. Using this data, all the E.C.Ps were then extracted for each device, at various gate-biases and Vds = 3V. Finally we have a model that can give the E.C.Ps of any device we fabricated, given the gate-bias, number of gate-fingers and gate-width. This equivalent circuit can be used to generate S-parameters of devices with good accuracy in the whole frequency range of measurement. ©2009 IEEE.